Periodic 1.5 ka climate variations during MIS 2 in the belt of Southern Hemispheric westerlies. Issue 1 (7th June 2017) - Kliem, Pierre; Baumgarten, Henrike; Gebhardt, Catalina; Hahn, Annette; Ohlendorf, Christian; Zolitschka, Bernd
Abstract: Lacustrine sediments retrieved from Laguna Potrok Aike in the framework of the Potrok Aike Maar Lake Sediment Archive Drilling Project (PASADO) offer the possibility to investigate climate variations of the past 51 cal ka BP in Southern Hemispheric midlatitudes, Argentinean Patagonia. This study focuses on short-term cyclicities in the Ca and magnetic susceptibility data sets between 51 and 15 cal ka BP. The record yields a climate pattern with a periodicity of 1.5 ka during Marine Oxygen Isotope Stage 2 (MIS 2) detected in the Southern Hemisphere from 31 to 17 cal ka BP for the first time. MIS 2 is known for constantly cold temperatures, whereas prominent climate variations paced by a 1.5 ka periodicity occurred during MIS 3. Our study documents that minor latitudinal oscillations of the Southern Hemispheric westerlies and the polar easterlies with a 1.5 ka periodicity also took place during MIS 2. However, we assume that because of a major northward displacement of the Southern Hemispheric westerlies, these oscillations did not sufficiently affect the zone of Circumpolar Deep Waters and an increased greenhouse effect by upwelling of CO2 -rich deep waters did not occur. This mechanism illustrates why prominent climate events fail to appear during MIS 2.